Establishing the risk factors of pantograf trolleybuses for electrification - Claudiu Babiş; Andrei Dimitescu (Journal of Research and Innovation for Sustainable Society)
The paper addresses two research directions: the first direction is an evolutionary study of the pantograph trolleybuses for electrification used by the railways in Romania. This direction makes an analysis of the competitiveness from several points of view: technological, economic, qualitative and managerial of the pantograph trolleybuses by the comparison method. The second direction of research is an analysis of the risk factors that occur in the use of pantograph trolleybuses as well as the accompanying static and dynamic equipment. Information will be presented regarding the description of the risk factors that will be analyzed.